PELAGIC LARVAE OF SOME POLYCHAETA IN THE WHITE SEA (PELAGICHESKIE LICHINKI NEKOTORYKH POLIKHET BELOGO MORYA) - Sveshnikov,V. A. (1968)
Pholoe minuta tecta Stimpson undergoes pelagic development in the White Sea. Its trochophora and metatrochophora possess a character typical of the pelagic larvae of all Aphroditidae, namely a bundle of long motionless cilia on the left side of the oral aperture. The larva has four larval segments on which only neuropodial sections of developing parapodia are well developed. Nereis virens Sars in the White Sea also undergoes pelagic development. The larva is characterized by the presence of 3 paratrochs and 4 larval segments on which both the neuropodial and notopodial sections of developing parapodia are equally well developed. Scoloplos armiger (O. F. Muller) in the White Sea lays single eggs into plankton where they undergo development up to the stage of metatrochophora. Characteristic features of the larvae belonging to this species are as follows: orange coloration, presence of several ciliar rings, paratrochs -- on each appearing segment, and leucitotrophous mode of feeding. Early stages of S. armiger were described by E. Smidt (1951) as the species Heteromastus filiformis Clap. (Author) Trans. of Zoologicheskii Zhurnal (USSR) v39 n3 p343-355 1960, by M. Slessers.